1997
DOI: 10.1097/00043764-199703000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Three Lumbar Sagittal Motion Measurement Methods

Abstract: Three surface methods for measuring lumbar sagittal motion (LSM) were tested for reliability. The three methods used were the Pleurimeter V double inclinometer, the carpenter double inclinometer, and the computerized single sensor inclinometer. In this study, 30 volunteers were examined independently by three occupational health professionals. Each volunteer rotated twice through three stations at which LSM was measured by each of the three methods. The intra- and interexaminer reliabilities in identifying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
0
14
1
1
Order By: Relevance
“…In a study using a single-sensor inclinometer, Chen et al(1997) 12) reported ICC=0.39 for extension and ICC=0.69 for bending in terms of interrater reliability, which are lower than the interrater reliabilities found in this study. Furthermore, Dopf et al(1994) 24) reported ICC=0.84 for extension and ICC=0.76 for bending in terms of interrater reliability using a spine motion analyzer, which are lower than the interrater reliabilities found in this study.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In a study using a single-sensor inclinometer, Chen et al(1997) 12) reported ICC=0.39 for extension and ICC=0.69 for bending in terms of interrater reliability, which are lower than the interrater reliabilities found in this study. Furthermore, Dopf et al(1994) 24) reported ICC=0.84 for extension and ICC=0.76 for bending in terms of interrater reliability using a spine motion analyzer, which are lower than the interrater reliabilities found in this study.…”
Section: Discussioncontrasting
confidence: 83%
“…Accordingly, devices to measure the treatment effectiveness of various spinal disorders through the skin surface are being developed 11) , as well as non-invasive techniques to measure spinal mobility, such as goniometer and inclinometer measurements to avoid the problem of repetitive radiation exposure [12][13][14] . A variety of devices have been developed and used for spinal motion assessment, ranging from measurements using a simple tape to computer application devices 13,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…This evaluation should include an investigation of signs and symptoms of spinal abnormalities and movement dysfunctions, especially of the lower back, utilizing standardized approaches and tests, i.e., the clinical evaluations further reviewed by NIOSH [1992], Nelson [1991], Borenstein and Wiesel [1989], Erdil and Dickerson [1997] or Viikari-Juntura et al [1998]. In general, the diagnostic accuracy and reliability of functional assessments and measurements can differ considerably between test methods, examiners, and even between subsequent exams of the same patient [Leclaire et al, 1996;Chen et al, 1997]. However, in a cooperative patient and with an experienced examiner, the following proposed tests are useful to adequately assess and describe spinal deformity, motion restrictions or painful abnormalities in order to establish a diagnosis and clinical treatment decisions.…”
Section: The Clinical Examination Of Workers With Low Back Complaintsmentioning
confidence: 99%
“…If clinicians aim to ‘normalise’ dysfunctional movement, they need an empirical basis for (i) differentiating between normal and dysfunctional movement, and (ii) determining whether correction of dysfunctional movement might reduce pain and activity limitation. Measurement of movement and posture has been problematic in typical clinical settings due to limitations (practicality, accuracy, comprehensiveness, reliability) of simple measurement tools such as goniometers, tape measures and inclinometers [7]. Advances in technology are creating new opportunities, available for use in typical clinical settings, that measure comprehensive information about the relationship between movement/posture and pain [8-10].…”
Section: Introductionmentioning
confidence: 99%